Real hypersurfaces with Reeb Jacobi operator of Codazzi type in the complex hyperbolic two-plane Grassmannians - Suh, Young Jin (MATHEMATICA SCANDINAVICA, 2025)
Utilizing the concept of Reeb Jacobi operator of Codazzi type, we investigate Hopf real hypersurfaces in the complex hyperbolic two-plane Grassmannian G^*_2(C^m+2) which admit a constant Reeb function α along the Reeb direction of ξ. If the Reeb function α is constant along the Reeb direction, then the Reeb vector field ξ =-JN either belongs to the distribution D or the distribution D^. By virtue of this fact, we have proved a new result about Reeb Jacobi operator of Codazzi type according to the Reeb vector field ξ D^ or ξ D, respectively.